Method for separating and characterizing inclusions in high-temperature alloy and return scrap

CN119804524AActive Publication Date: 2025-04-11UNIV OF SCI & TECH BEIJING

Patent Information

Application Number
CN202411862449.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-11
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The prior art is difficult to accurately detect the types, compositions, sizes and morphology of non-metallic inclusions in high-temperature alloys, and traditional methods cannot effectively remove γ' and MC-type carbides in the alloy.

Method used

The sample electrolysis method combined with the ICP-MS test method was used to separate non-metallic inclusions by electrolysis, and qualitatively characterized by XRD and SEM, and γ′ and MC type carbides were removed through repeated washing processes.

Benefits of technology

Accurate quantitative characterization of non-metallic inclusions in high-temperature alloys is realized, and the γ′ and MC type carbides in the alloy can be effectively removed, thereby improving the cleanliness and reuse of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119804524A_ABST
    Figure CN119804524A_ABST
Patent Text Reader

Abstract

The invention discloses a separation and characterization method for inclusions in high-temperature alloy and return scraps, and relates to the technical field of high-temperature structural materials and application. The method comprises the following steps: preparing an electrolyte according to x% (NH4) 2SO4, x% C6H5O7 (NH4) 3, 2x% C6H8O7 and the balance of deionized water and x = 1.5-2.0 (mass percent), performing an electrolysis process and a separation process on a small-size sample, extracting the non-metallic inclusions in the sample, and combining an inductively coupled plasma mass spectrometry (ICP-MS) test method to obtain the content of elements contained in the inclusions. And finally, calculating the contents of various inclusions according to the element contents. By means of the method, the small-size inclusions can be obtained, meanwhile, the types and the content of the inclusions can be accurately measured, and a reasonable and feasible cleanliness evaluation method is provided for high-temperature alloy smelting preparation enterprises.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of high temperature structural materials and application technology, in particular to high temperature alloy return materials, and specifically to an experimental method for electrolytic separation and quantitative characterization of non-metallic inclusions in high temperature alloys. Background Art

[0002] High-temperature alloys are widely used in aircraft engines and gas turbines as key parts such as turbine blades and casings. In order to ensure the safe life and reliability of engines and aircraft, it is particularly important to prepare ultra-pure and defect-free high-temperature alloy materials. The cleanliness of high-temperature alloys is mainly affected by non-metallic inclusions. Non-metallic inclusions in high-temperature alloys mainly exist in non-metallic compound states, including oxides of components such as Al, Si, Ca, Mg, TiN nitrides, and composite inclusions of the two. These inclusions mostly come from deoxidation products in the smelting process, erosion of refractory materials such as crucibles, and precipitation during the solidification process.

[0003] The material utilization rate of cast high-temperature alloys and their parts is usually only 10%-20%, and the amount of cast high-temperature alloy return materials produced in my country each year is as high as thousands of tons. Since the castings undergo a high-temperature melting process, the alloy melt contacts and reacts with the crucible, core, shell, filter, etc. at high temperatures, resulting in the return materials usually containing more inclusions and impurity elements than new materials. Accurately characterizing the types and quantities of inclusions and providing high-quality recycled raw materials for later smelting is the key to the recycling of return alloys.

[0004] There are specific standards for the determination of non-metallic inclusions in steel at home and abroad, among which ASTME45-2018 "Standard Test Methods for Determining the Inclusion Content of Steel" is the most widely used. This standard is applicable to determining the content of non-metallic inclusions in forged steel. The morphology is observed by using polarized light, bright field, and dark field of an optical microscope, and compared with the standard atlas. The worst field of view method is used to rate the non-metallic inclusions in the cross section. This method is one of the key technical standards for testing non-metallic inclusions in steel, but this standard is not applicable to high-temperature alloys with extremely low oxygen and nitrogen content, and is limited to a two-dimensional plane, making it difficult to reflect the overall material.

[0005] At present, most high-temperature alloy smelting and preparation companies usually conduct inclusion detection according to the navigation mark HB 5406-2012 standard. This standard takes a 3.5-4.5kg ingot at the upper position after the shrinkage cavity is cut off once, and performs a smelting operation at a smelting temperature exceeding the alloy liquidus temperature. The percentage of slag area is quantitatively calculated by electronic recording to represent the minimum purity level of the entire furnace alloy ingot. As an important basis for evaluating the purity of high-temperature alloys, this standard plays a key role in the detection of high-temperature alloy inclusions, but this method cannot obtain characteristic information such as the type, composition, size and morphology of inclusions in the alloy.

[0006] Chinese patent ZL 201210276465.0 proposes a method for determining large non-metallic inclusions in steel by electrolysis. Sufficient oxide inclusions are separated through steps such as electrolysis preparation, electrolysis, elution, reduction, magnetic separation, inclusion classification and weighing. This method uses grading and weighing to quantitatively detect the inclusion content in steel, which has the advantages of large test samples and strong representation of inclusions. However, this method cannot collect inclusions smaller than 10μm, the electrolyte contains Fe elements, resulting in Fe contamination in the collected inclusions, and the elution method is difficult to separate carbides and inclusions.

[0007] Based on the large sample electrolysis method, Chinese patent ZL 202311124486.5 proposes a method for characterizing non-metallic inclusions by small sample electrolysis for DZ125 nickel-based high-temperature alloy. This method uses a salt containing oxygen-containing acid radicals that does not contain Fe as an electrolyte to electrolyze the alloy test rod, collects the anode mud obtained by electrolysis with a semipermeable membrane with a pore size of 0.45μm, and then separates the inclusions by pickling. Subsequently, the non-metallic inclusions in the alloy are quantitatively characterized by calculating the weight of the electrolyzed inclusions and the sample consumed by electrolysis, and the morphology and size of the inclusions are observed using a scanning electron microscope, and the phase composition of the inclusions is analyzed using the energy spectrometer of the scanning electron microscope. This method can obtain small-sized inclusions, but it cannot accurately obtain the composition and content of various types of inclusions.

[0008] Based on the above background, it is necessary to develop a method suitable for the electrolytic separation and quantitative characterization of non-metallic inclusions in high-temperature alloys and their return materials, which can not only electrolyze and separate non-metallic inclusions from carbides in alloys in a relatively short time, but also quantitatively characterize the types and compositions of inclusions and the contents of various types of inclusions. Summary of the invention

[0009] The purpose of the present invention is to provide an experimental method for electrolytic separation and quantitative characterization of non-metallic inclusions in high-temperature alloys and their return materials. A small-sized sample is subjected to an electrolytic process and a separation process to extract non-metallic inclusions in the sample. Combined with an inductively coupled plasma mass spectrometry (ICP-MS) test method, the element content contained in the inclusions is obtained. Finally, the content of various inclusions is calculated based on the element content. The present invention can not only obtain small-sized inclusions, but also accurately determine the type and content of the inclusions.

[0010] The embodiments of the present invention are as follows:

[0011] A method for separating inclusions in a high-temperature alloy and a return material mainly comprises the following steps:

[0012] 1) Obtain the sample of return material or alloy ingot for electrolysis: weigh the sample before electrolysis.

[0013] 2) Prepare the electrolyte: calculated by mass percentage, x% (NH4)2SO4 + x% C6H5O7(NH4)3 + 2x% C6H8O7 + balance deionized water, x = 1.5-2.0.

[0014] 3) Electrolysis process: room temperature constant voltage electrolysis, current density is 0.025-0.05A / cm 2 , put the electrolyte in multiple containers, record them as A-1, A-2, A-3..., immerse the sample in the electrolyte, and replace them with A-2, A-3... at regular intervals, until the sample immersed in the electrolyte disappears completely. The electrolysis process is over, dry the sample that is not immersed in the electrolyte, regard it as the sample after electrolysis, and weigh it.

[0015] 4) Separation process 1: Calculate by volume percentage, add 3-5% concentrated H2SO4 to containers A-1, A-2, A-3..., respectively, and add 1-3% C4H4O6 to containers A-1, A-2, A-3..., respectively, and heat in a water bath at 85-95°C for 2-4 hours. Let stand for more than 4 hours, siphon off the supernatant (dark green), mix the remaining black precipitates in containers A-1, A-2, A-3... into solution A, then add deionized water to solution A, and repeat the above separation process 2-4 times. Separation process 1 is completed.

[0016] 5) Separation process 2: Add deionized water to solution A, add 5-10% concentrated H2SO4 to solution A by volume percentage, then add 5-15% H2O2, heat in a water bath at 85-95℃ for 2-4h, add H2O2 at regular intervals during heating (add until the solution turns orange), and siphon out the upper layer of liquid after heating is completed; then continue to add deionized water to solution A, and at the same time, add 5-10% concentrated H2SO4 to solution A by volume percentage, add saturated KMnO4 dropwise until the solution turns purple-red and no longer becomes lighter, heat in a water bath at 85-95℃ for 2-4h, and add saturated KMnO4 at regular intervals during heating (add until the solution turns purple-red). After heating is completed, add saturated oxalic acid until the solution turns from purple to white; finally, put solution A into an ultrasonic machine for 5-10min ultrasonic cleaning, and then siphon out the upper white solution. Repeat ultrasonic cleaning and siphoning 2-4 times, and separation process 2 is completed.

[0017] 6) Separation process 3: Continue to separate solution A, you can choose to use one of the following methods, or you can use both methods in a cycle, until the black precipitate in solution A is basically completely dissolved, the white precipitate appears, and the white powder sample containing inclusions is separated, and separation process 3 is completed.

[0018] One method is to add deionized water to solution A, and add 5-10% concentrated H2SO4 and 10-20% H2O2 to solution A by volume to maintain the orange color of the solution. Heat the solution in a water bath at 85-95°C for 2-4 hours. After heating, use a suction filtration device to filter the solution, and rinse the filtered precipitate back into solution A.

[0019] The second method is to add deionized water to solution A, add 5-10% concentrated H2SO4 to solution A by volume percentage, add saturated KMnO4 dropwise until the purple-red color remains and no longer becomes lighter, heat in a water bath at 85-95°C for 2-4 hours, and after heating, add saturated oxalic acid until the solution changes from purple to clear, filter using a suction device, and rinse the filtered precipitate back into solution A.

[0020] Furthermore, the returned material or alloy ingot in step 1) can retain the original surface, and the surface oxide layer needs to be polished off when using electric spark cutting. The preferred shape is cylindrical or long strip, with a diameter not greater than 20 mm, a length not greater than 80 mm or a long strip of the same proportion, and a weight not greater than 200 g.

[0021] Furthermore, in step 3), the electrolyte is replaced every 22-26 hours.

[0022] Furthermore, in step 4), 500-800 ml of deionized water is added to solution A; in step 5), 200-500 ml of deionized water is added to solution A; and in step 6), 100-300 ml of deionized water is added to solution A.

[0023] Furthermore, the recycling of the two methods in step 6) is based on the specific reduction of the black precipitate. After separation by method one, method two can also be used for separation. If the effect of reducing the black precipitate is still not good, method one can be used for separation again.

[0024] Furthermore, the filtration in step 6) is performed using a 0.22 μm microporous filter membrane.

[0025] Furthermore, it is necessary to simultaneously carry out electrolytic separation of the two groups of samples to obtain two groups of precipitates, one group of precipitates is used for XRD and SEM qualitative characterization, and the other group of precipitates is used for ICP-MS quantitative characterization.

[0026] The qualitative characterization method of the above inclusion powder sample is as follows:

[0027] 1) Use a suction filtration device to filter out the precipitate (non-metallic inclusions) in solution A and store the precipitate on a microporous filter membrane.

[0028] 2) Use transparent tape to fix the microporous filter membrane on the sample stage and perform X-ray diffraction (XRD) characterization to determine the type and crystal structure of non-metallic inclusions and obtain the content ratio of each type of non-metallic inclusions.

[0029] 3) Use a microporous filter membrane to lightly touch the conductive adhesive and perform scanning electron microscope energy spectrum (SEM-EDS) characterization to obtain the type, morphology, size and other characteristics of non-metallic inclusions in the high-temperature alloy.

[0030] The quantitative characterization method of the above inclusion powder sample is as follows:

[0031] 1) Use slow quantitative filter paper to filter the solution and precipitate in the beaker, and perform ICP-MS component test on the filter paper and precipitate to obtain the mass concentration of each element ρ M , unit: μg / ml.

[0032] 2) Calculate the mass fraction of the element in wt.%, where ρ M is the mass concentration of the element, in μg / ml; m1 is the mass of the sample before electrolysis, in g; m2 is the mass of the sample after electrolysis, in g; V is the volume of the test solution used in ICP-MS test, in ml.

[0033] 3) Calculate the mass fraction of inclusions ω2, in wt.%, Where M1 is the molar mass of the element, in g / mol; M2 is the molar mass of the inclusion, in g / mol.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The traditional electrolysis method uses the weight of inclusions / the weight of the sample consumed by electrolysis as the content of inclusions, and cannot subdivide the composition, type and content of the inclusions. The inclusions separated by electrolysis of the present invention can be identified by using XRD, and the percentage of elements contained in the inclusions can be obtained by the ICP-MS component testing method, and then the proportion of each type of inclusions can be calculated.

[0036] The advantages of the present invention are that the anode mud obtained by electrolysis is repeatedly washed with KMnO4 and H2O2 under high temperature and acidic conditions, so that γ′ and MC carbides in the alloy can be effectively removed; small-sized inclusions can be obtained by performing XRD and SEM tests, and the types and crystal structures of various non-metallic inclusions in the alloy can be qualitatively characterized; and the separated powder can be subjected to ICP-MS testing to quantitatively characterize the contents of various non-metallic inclusions in the alloy;

[0037] In addition, the present invention has a wide application area and no restrictions on sampling. It can quantitatively characterize the inclusions in different parts of high-temperature alloy master alloy ingots and various types of high-temperature alloy return blocks. The results are more accurate and reliable, providing a reasonable and feasible cleanliness assessment method for high-temperature alloy smelting and preparation companies. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The present invention is a flow chart of the method for electrolytic separation and qualitative and quantitative characterization of non-metallic inclusions in high-temperature alloys.

[0039] Figure 2 This is the XRD diffraction pattern of inclusions extracted in the example.

[0040] Figure 3 The SEM-SE / BSE images, EDS element surface scan images, and energy spectrum images of some inclusions extracted in the example are shown. Figure 3 (a) is the secondary electron mode imaging image, Figure 3 (b) is the backscattering mode imaging image, Figure 3 (cf) are the element distribution diagrams of C, O, Al and Si respectively. Figure 3 (gi) are the energy spectra of the three positions indicated by the arrows. DETAILED DESCRIPTION

[0041] 1) Obtain the sample for electrolysis: Use spark cutting to return the alloy material. The size of the electrolysis sample is about 50 mm in length, 18 mm in width, and 12 mm in height. Use an electronic balance to weigh the weight of the sample before electrolysis and record it as m1, m1=78.1214 g.

[0042] 2) Prepare the electrolyte: calculated by mass percentage, 1.5% (NH4)2SO4 + 1.5% C6H5O7(NH4)3 + 3% C6H8O7 + the remainder deionized water.

[0043] 3) Electrolysis process: room temperature, assembled electrolysis device, constant voltage electrolysis, current density of 0.04A / cm 2 , the beaker containing electrolyte in the electrolysis device is a 1L beaker. Add 800ml of electrolyte to beaker A-1, use a glass rod to scratch the sample and add electrolyte to 800ml every 8 hours, replace the new electrolyte every 24 hours, and the beaker containing the new electrolyte is marked as A-2 (marked as A-3... in sequence). After three days of electrolysis, the sample immersed in the electrolyte completely disappears, and the electrolysis process is over. Dry the sample that is not immersed in the electrolyte and regard it as the sample after electrolysis. Weigh the weight of the sample after electrolysis and record it as m2, m2=29.6479g.

[0044] 4) Separation process 1-1: Calculate by volume percentage, add 5% concentrated H2SO4 to beakers A-1, A-2, and A-3 respectively, and then add 3% C4H4O6 by mass percentage. Heat in a water bath at 85°C for 3 hours, let stand for 4 hours, siphon off the supernatant (dark green), mix the remaining black precipitates in beakers A-1, A-2, and A-3 into beaker A (capacity of 1 L), and mark it as solution A.

[0045] 5) Separation process 1-2: Add deionized water to beaker A to 800 ml, add 5% concentrated H2SO4 by volume, and then add 3% C4H4O6 by mass, heat in a water bath at 85°C for 2 hours, let stand for 4 hours, and siphon off the supernatant. After repeating separation process 1-2 twice, the color of the siphoned supernatant turns light green, and separation process 1-2 is completed.

[0046] 6) Separation process 2-1: Add deionized water to beaker A to make it 400 ml, add 5% concentrated H2SO4 and 5% H2O2 to beaker A by volume percentage, heat in a water bath at 85-95°C for 4 hours, and add H2O2 every half an hour during heating (add until the solution turns orange). After heating, siphon off the upper liquid.

[0047] 7) Separation process 2-2: Add deionized water to beaker A to make it 400 ml, add 5% concentrated H2SO4 to beaker A by volume percentage, add saturated KMnO4 dropwise until the solution turns purple-red and no longer becomes lighter, heat in a water bath at 85-95°C for 4 hours, and add saturated KMnO4 every half an hour during heating (add until the solution turns purple-red). After heating, add saturated oxalic acid until the solution turns from purple to white.

[0048] 8) Separation process 2-3: Place beaker A in an ultrasonic machine for 5 minutes of ultrasonic cleaning, and then immediately siphon off the upper white solution. After repeating separation process 2-3 three times, the color of the siphoned upper solution turns pale white, close to clear.

[0049] Clear, separation process 2-3 is completed.

[0050] 9) Separation process 3: Add deionized water to beaker A to make it 200 ml. Calculate by volume percentage, add 5%

[0051] Concentrated H2SO4, add 15% H2O2, add H2O2 every 1h during heating (to keep the solution orange), heat in 85℃ water bath for 3h, after heating, use suction filtration device to filter, after filtration, rinse the filtered precipitate back to A

[0052] beaker. At this time, a large amount of black precipitate disappears. Continue to add deionized water to beaker A to 200ml, add 5% concentrated H2SO4 to beaker A by volume percentage, and add saturated KMnO4 until the purple-red color no longer becomes lighter. No saturated KMnO4 is added during heating (the solution remains purple-red), and heat in a water bath at 85°C for 2h. After heating, add saturated oxalic acid until the solution changes from purple to clear, and use a suction filtration device for suction filtration. After the filtration is completed, rinse the filtered precipitate back into beaker A. Repeat the above process once, the black precipitate no longer decreases, and a large amount of white precipitate exists, and the separation process is completed.

[0053] The qualitative characterization method of the above inclusion powder sample is as follows:

[0054] 10) Use a suction filtration device to filter the precipitate (non-metallic inclusions) in beaker A and store the precipitate on a microporous filter membrane.

[0055] 11) Use transparent tape to fix the microporous filter membrane on the sample stage and perform X-ray diffraction (XRD) characterization to determine the type of non-metallic inclusions. Figure 2 This is the X-ray diffraction pattern of the extracted inclusions. The results show that the inclusions mainly include: HfO2, Al2(SiO4)O, and Al2O3.

[0056] 12) Use a microporous filter membrane to lightly touch the conductive adhesive and perform scanning electron microscope energy spectrum (SEM-EDS) characterization to obtain the type, morphology, size and other characteristics of non-metallic inclusions in the high-temperature alloy. Figure 3 (b) Backscattering mode imaging combined with Figure 3 (cf) element surface distribution results, Figure 3 The energy spectrum of (gi) and the element point scan data in Table 1 can be obtained Figure 3 The three inclusion particles pointed by the black arrows in (a) are Al2(SiO4)O, Al2O3, and SiO2. Figure 3

[0057] The secondary electron mode imaging in (a) shows their morphological size information. Al2(SiO4)O inclusions are in the form of flocs, Al2O3 inclusions are in the form of flakes, and SiO2 inclusions are in the form of blocks. The sizes of the three are all around 10 microns. Figure 3 It is only a very small part of the numerous inclusion particles. Through more SEM-EDS characterization in the future, more information on the morphology, size, type, etc. of the inclusion particles can be obtained. Figure 3 Smaller particles (<1 μm) can be found, so the electrolytic separation method can retain small inclusions. The characterization results are basically consistent with the characterization results in step 11), so the corresponding oxide inclusion content can be estimated by element content in steps 13), 14), and 15).

[0058] The quantitative characterization method of the above inclusion powder sample is as follows:

[0059] 13) ICP-MS test: Use slow quantitative filter paper to filter the white precipitate and solution in the beaker, put the filter paper and precipitate into a platinum crucible, incinerate in a muffle furnace at 1000°C for 1h, add 2g mixed flux (30% H3BO3+70% Na2CO3, calculated by mass) to cover the sample, heat and melt at 800°C for 10min, cool and place in 100mL 5% concentrated

[0060] Dissolve in HCl (calculated by volume) solution, dilute to constant volume and use ICP-MS to test the composition. The mass concentration of each element is obtained. M , unit μg / ml. Al element mass concentration 2.29μg / ml, Ca element mass concentration 2.40

[0061] μg / ml, Mg element mass concentration 0.40μg / ml, Si element mass concentration 9.10μg / ml, Hf element mass concentration

[0062] 4.52μg / ml.

[0063] 14) Calculate the mass fraction ω1 of the element in wt.%. where ρ M is the mass concentration of the element, in μg / ml; m1 is the mass of the sample before electrolysis, in g, m1=78.1214g; m2 is the mass of the sample after electrolysis, in g, m2=29.6479g; V is the total volume of the test solution, in ml, V=100ml. Taking Al as an example, the mass concentration is 2.29μg / ml, and the mass fraction is Similarly, the mass fraction of Ca element is 0.00050%; the mass fraction of Mg element is 0.00008%; the mass fraction of Si element is 0.00188%; the mass fraction of Hf element is 0.00093%;

[0064] 15) Calculate the mass fraction of inclusions, ω2, in wt.%. Where M1 is the molar mass of the element, in g / mol; M2 is the molar mass of the inclusion, in g / mol. Taking Al2O3 as an example, the mass fraction Similarly, the mass fraction of CaO is 0.00069%; the mass fraction of MgO is 0.00014%; the mass fraction of SiO2 is 0.00429%; and the mass fraction of HfO2 is 0.00110%.

[0065] Table 1 Figure 3 The EDS point scan data at the position indicated by the red arrow can be used to semi-quantitatively analyze the elemental composition and type of inclusions.

[0066] Table 2 shows the concentration of each element obtained by ICP-MS test. According to steps 14) and 15), the mass fraction of each type of inclusion in the alloy return material can be calculated.

[0067] Through the implementation of this example, it was found that this separation method can preserve small inclusions larger than 0.5 μm, and ICP-

[0068] The element detection accuracy of MS is 0.01 μg / mL.

[0069] Table 1

[0070]

[0071] Table 2

[0072] Measured elements Solution concentration μg / ml Element mass fraction wt.% Corresponding inclusion type Oxide mass fraction wt.% Al 2.29 0.00047 <![CDATA[Al2O3]]> 0.00089 Ca 2.40 0.00050 CaO 0.00069 Mg 0.40 0.00008 MgO 0.00014 Si 9.10 0.00188 <![CDATA[SiO2]]> 0.00429 Hf 4.52 0.00093 <![CDATA[HfO2]]> 0.00110 Ta 2.24 0.00046 Ti 0.73 0.00015 Co 0.18 0.00004 Cr 0.41 0.00008 Mo 0.39 0.00008 W 0.79 0.00016 Ni 0.57 0.00012

Claims

1. A method for separating inclusions from high-temperature alloys and return materials, characterized in that: The main steps include: 1) Obtain the sample of the return material or alloy ingot for electrolysis: weigh the weight of the sample before electrolysis; 2) Prepare electrolyte: calculated by mass percentage, x% (NH4)2SO4+x% C6H5O7(NH4)3+2x% C6H8O7+balance deionized water, x=1.5-2.0; 3) Electrolysis process: room temperature constant voltage electrolysis, current density is 0.025-0.05A / cm 2 , put the electrolyte in multiple containers, record them as A-1, A-2, A-3..., immerse the sample in the electrolyte, and replace them with A-2, A-3... at regular intervals, until the sample immersed in the electrolyte disappears completely, the electrolysis process is over, dry the sample not immersed in the electrolyte, regard it as the sample after electrolysis, and weigh it; 4) Separation process 1: Calculate by volume percentage, add 3-5% concentrated H2SO4 to containers A-1, A-2, A-3... respectively, and add 1-3% C4H4O6 to containers A-1, A-2, A-3... respectively, heat in a water bath at 85-95°C for 2-4h, let stand for more than 4h, siphon off the supernatant, mix the remaining black precipitates in containers A-1, A-2, A-3... into solution A, then add deionized water to solution A, repeat the above separation process 2-4 times, and separation process 1 is completed; 5) Separation process 2: add deionized water to solution A, add 5-10% concentrated H2SO4 to solution A by volume percentage, then add 5-15% H2O2, heat in a water bath at 85-95°C for 2-4h, add H2O2 at regular intervals during heating until the solution turns orange, and after heating, siphon off the upper layer of liquid; then continue to add deionized water to solution A, and at the same time, add 5-10% concentrated H2SO4 to solution A by volume percentage, add saturated KMnO4 dropwise until the solution turns purple-red and no longer becomes lighter, heat in a water bath at 85-95°C for 2-4h, add saturated KMnO4 at regular intervals during heating until the solution turns purple-red, and after heating, add saturated oxalic acid until the solution turns from purple to white; finally, put solution A into an ultrasonic machine for 5-10min ultrasonic cleaning, then siphon off the upper white solution, repeat ultrasonic cleaning and siphoning 2-4 times, and separation process 2 ends; 6) Separation process 3: continue to separate solution A, select one of the following methods, or use both methods in a cycle, until the black precipitate in solution A is basically completely dissolved, the white precipitate appears, and the white powder sample containing inclusions is separated, and separation process 3 is completed; One method is to add deionized water to solution A, add 5-10% concentrated H2SO4 and 10-20% H2O2 to solution A by volume percentage, keep the solution orange, heat it in a water bath at 85-95℃ for 2-4h, and after heating, use a suction filter to filter, and rinse the filtered precipitate back into solution A; The second method is to add deionized water to solution A, add 5-10% concentrated H2SO4 to solution A by volume percentage, add saturated KMnO4 dropwise until the purple-red color remains and no longer becomes lighter, heat in a water bath at 85-95°C for 2-4 hours, and after heating, add saturated oxalic acid until the solution changes from purple to clear, filter using a suction device, and rinse the filtered precipitate back into solution A.

2. The inclusion separation method according to claim 1, characterized in that: Step 1) The returned material or alloy ingot can retain the original surface, and the surface oxide layer needs to be polished off when using electric spark cutting. The shape is cylindrical or long strip, with a diameter of no more than 20mm, a length of no more than 80mm or a long strip of the same proportion, and a weight of no more than 200g.

3. The inclusion separation method according to claim 1, characterized in that: Step 3) The electrolyte is replaced every 22-26 hours.

4. The inclusion separation method according to claim 1, characterized in that: In step 4), 500-800 ml of deionized water is added to solution A; in step 5), 200-500 ml of deionized water is added to solution A; in step 6), 100-300 ml of deionized water is added to solution A.

5. The inclusion separation method according to claim 1, characterized in that: Step 6) The two methods are cyclically used according to the reduction of black precipitate. After separation by method one, separation by method two is performed. If the effect of reducing black precipitate is still not good, separation by method one is performed again.

6. The inclusion separation method according to claim 1, characterized in that: Step 6) The filtration is performed using a 0.22 μm microporous filter membrane.

7. The inclusion separation method according to claim 1, characterized in that: The two groups of samples were electrolytically separated simultaneously to obtain two groups of precipitates. One group of precipitates was used for qualitative characterization by XRD and SEM, and the other group of precipitates was used for quantitative characterization by ICP-MS.

8. The method for characterizing inclusions according to any one of claims 1 to 7, characterized in that: The inclusion powder sample was qualitatively characterized by the following method: 1) Use a suction filtration device to filter the precipitate (non-metallic inclusions) in solution A and store the precipitate on a microporous filter membrane; 2) Use transparent tape to fix the microporous filter membrane on the sample stage and perform X-ray diffraction (XRD) characterization to determine the type and crystal structure of non-metallic inclusions and obtain the content ratio of various non-metallic inclusions; 3) Use a microporous filter membrane to lightly touch the conductive adhesive and perform scanning electron microscope energy spectrum (SEM-EDS) characterization to obtain the type, morphology, size and other characteristics of non-metallic inclusions in the high-temperature alloy.

9. The method for characterizing inclusions according to any one of claims 1 to 7, characterized in that: The inclusion powder sample was quantitatively characterized by the following method: 1) Use slow quantitative filter paper to filter the solution and precipitate in the beaker, and perform ICP-MS component test on the filter paper and precipitate to obtain the mass concentration of each element ρ M , unit: μg / ml; 2) Calculate the mass fraction of the element in wt.%, where ρ M is the mass concentration of the element, in μg / ml; m1 is the mass of the sample before electrolysis, in g; m2 is the mass of the sample after electrolysis, in g; V is the volume of the test solution used for ICP-MS test, in ml; 3) Calculate the mass fraction of inclusions ω2, in wt.%, Where M1 is the molar mass of the element, in g / mol; M2 is the molar mass of the inclusion, in g / mol.

Citation Information

Patent Citations

  • Analytical method of small-size impurities in steel

    CN102095671A

  • Method for extracting and observing three-dimensional appearance of non-metallic inclusion in steel in full-scale mode

    CN102538703A

  • Method for separating non-metallic inclusion and carbide from steel inclusion

    CN107328619A

  • Quantitative characterization method of non-metal inclusions in nickel-based high-temperature alloy powder

    CN107607567A

  • Classified extraction and quantitative analysis method for non-metallic inclusions in high-temperature alloy

    CN111238916A

Cited By

  • Preparation method of TiAl alloy casting containing return scraps

    CN121006441A

  • A method for producing a TiAl alloy casting containing return material

    CN121006441B